Organizational and legal guarantees for protection of human rights in the context of the constitutional and legal policy of Ukraine - Ternavska , Viktoriia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The rights and freedoms of man and citizen constitute the content of the constitutional and legal policy of every civilized state; they must be specific and provided with guarantees of implementation and protection. Nowadays, this issue is actualized in the context of the Russian Federation’s military aggression against Ukraine, in result of which millions of Ukrainian citizens are affected. There distinguished general and special guarantees in the system of human rights guarantees, where organizational and legal (institutional) guarantees have the particular importance, since the only embodying the rights and freedoms in normative legal acts does not guarantee a person the possibility of implementing and effectively protecting all these rights and freedoms. Organizational and legal (institutional) guarantees are statutory defined state and non-state institutions that protect human and civil rights and freedoms at the national and international levels by jurisdictional and non-jurisdictional means. It is asserted that the most efficient institutions in the system of organizational and legal guarantees are the Commissioner for Human Rights of the Verkhovna Rada of Ukraine as well as advocacy, mediation and human rights NGOs as independent institutions that carry out human rights activity both at the national and international levels. This joint action results to the periodic releasing the Ukrainian military personnel from Russian captivity, returning illegally detained civilians and forcibly removed Ukrainian children from the territory of the Russian Federation and temporarily occupied territories. It is concluded that despite the effective work of state and non-state institutions there remained some issues that can be resolved exclusively through the courts, in particular, the protection of the human dignity of Ukrainian citizens. Thus, one of the significant tasks of current constitutional and legal policy is to improve the entire mechanism for ensuring the rights and freedoms of man and citizen, where one of the important elements is the guarantees for protection.